2021
DOI: 10.33774/chemrxiv-2021-r72x1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Collision-Induced Unfolding of Native-like Protein Ions Within a Trapped Ion Mobility Spectrometry Device

Abstract: Native mass spectrometry and collision-induced unfolding (CIU) workflows continue to grow in utilization due to their ability to rapidly characterize protein conformation and stability. To perform these experiments, the instrument must be capable of collisionally activating ions prior to ion mobility spectrometry (IMS) analyses. Trapped ion mobility spectrometry (TIMS) is an ion mobility implementation that continues to grow in utilization due to its inherently high resolution and reduced instrumental footprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
4
10
0
Order By: Relevance
“…Incrementally increasing the Δ6 voltage above this value gradually recruits more charge states to dissociate (Figure 2A, S4A, and S5A). As shown in our previous manuscripts, 17,33 increased tunnel-in pressure has a negative impact on dissociation.…”
Section: Characterizing the Relationship Of Cidtims And Tunnel Pressuresupporting
confidence: 74%
See 2 more Smart Citations
“…Incrementally increasing the Δ6 voltage above this value gradually recruits more charge states to dissociate (Figure 2A, S4A, and S5A). As shown in our previous manuscripts, 17,33 increased tunnel-in pressure has a negative impact on dissociation.…”
Section: Characterizing the Relationship Of Cidtims And Tunnel Pressuresupporting
confidence: 74%
“…We further characterized the relationship of tunnel-in pressure and Δ6 by examining the collision-induced unfolding of protein ions and found that higher pressures limited the maximum internal energy and degree of protein conformational isomerization. 33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incrementally increasing the Δ6 voltage above this value at 1.5 mbar gradually recruits more ubiquitin charge states to dissociate until five charge state are fully depleted at 150 V (Figure 2A). As demonstrated in our previous manuscripts, 17,33 increased tunnel-in pressure has an inverse relationship with ion activation and only the 14+ and 13+ charge states of ubiquitin dissociate at 2 mbar even when the highest value of Δ6 is applied (Figure 2A). Similar trends in ion dissociation are observed for CytC, and βLG as they are subjected to Δ6 activation at various tunnel-in pressures (Figure S4A and S5A).…”
Section: Characterizing the Relationship Of Cidtims And Tunnel Pressuresupporting
confidence: 72%
“…Indeed, increasing the temperature (i.e., through collisional activation) of compact cytochrome c structures in the gas phase does produce extended states that compact down to the original CCS values, with the compact structures displaying a "permanent" increase in CCS. [58][59] With these considerations, the most accurate modeling of gaseous structures of well-folded proteins would need to keep temperatures low enough that the gas phase rearrangement barriers are not reached. Additionally, using the crystal structure of folded proteins, followed by relaxation in the gas phase, accurately reproduces experimental observables.…”
Section: Resultsmentioning
confidence: 99%